It Takes a Community to Educate Resilient Changemakers - Marita Coppes (Journal of the European Honors Council)
The educational landscape is evolving rapidly, with societal and technological challenges increasing the demand for resilient and adaptable students. This paper explores how the Global Project and Change Management (GPCM) honors program at Windesheim University integrates resilience-building into its curriculum through the Resiliency Labs. These labs leverage experiential learning and the Inner Development Goals (IDG) framework, combined with elements of Self-Determination Theory (SDT) —autonomy, competence, and relatedness—to foster intrinsic motivation and personal growth. By embedding both the IDGs and SDT principles into educational practices, we equip students with academic knowledge and the resilience needed to navigate complex global challenges.